Pengaruh Kompetensi dan Kepemimpinan Terhadap Komitmen Organisasi Pegawai Samsat Kabupaten Pidie dan Pidie Jaya Dengan Kepuasan Kerja Sebagai Variabel Mediasi - Herryzal Herryzal; Cecep Yoto Haryoto (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study investigates the influence of competence and leadership on organizational commitment, with job satisfaction serving as a mediating variable. The research was conducted among employees of SAMSAT agencies in Pidie and Pidie Jaya districts, involving 113 respondents from the Police and Jasa Raharja through a total sampling method. Data analysis was carried out using SEM. The results demonstrate that both competence and leadership have a positive and significant effect on job satisfaction and organizational commitment. This indicates that higher competence and effective leadership increase employee satisfaction, which in turn strengthens their commitment to the organization. Moreover, job satisfaction was found to significantly mediate the relationship between competence, leadership, and organizational commitment. In conclusion, enhancing human resources through improved technical skills and leadership qualities directly contributes to the development of a supportive and satisfying work environment. Such conditions encourage employee loyalty and foster stronger organizational attachment. These findings provide practical implications for formulating employee development strategies to promote a productive and sustainable work culture in the public service sector.